Integrasi Model Creative Problem Solving dan Pendekatan Deep Learning dalam Pembelajaran Fisika: Systematic Literature Review - Monika Ruth Cahayana; Endang Purwaningsih; Sunaryono; Anggita Meilina Putri; Kafa Pramitha Anggraini Indhira Artanti; Muhammad Ikhbar Ihshan (Postgraduate, University of Mataram, 2026)
Physics education in the 21st century requires learning approaches that promote creative thinking and problem-solving skills while fostering meaningful understanding. This study aims to analyze the integration of the Creative Problem Solving (CPS) model and the deep learning approach (as a pedagogical strategy emphasizing conceptual understanding rather than artificial intelligence) in physics education. This study employed a Systematic Literature Review (SLR) method following the PRISMA guidelines. A total of 124 articles published between 2018 and 2025 were identified from the SINTA and Scopus databases, of which 8 articles met the inclusion and quality criteria. The results indicate that the CPS model is effective in enhancing creative thinking skills, problem-solving abilities, and conceptual understanding in physics learning, while the deep learning approach strengthens conceptual understanding through meaningful and reflective learning processes. Furthermore, the integration of CPS and deep learning demonstrates potential in facilitating structured problem-solving processes supported by deeper conceptual engagement. In conclusion, the integration of CPS and deep learning can improve the quality of physics learning and contribute to the achievement of SDG 4 (Quality Education) by promoting higher-order thinking skills and meaningful learning experiences.